The Psychological Condition of STIQ Amuntai Student’s in Learning Arabic - Rifa'i, Ahmad; Hidayati, Erma; Purnamasari, S. (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2021)
This study discussed  the psychological condition  of STIQ Amuntai students in learning Arabic and the factors that  affect the psychological condition of STIQ Amuntai students in learning Arabic. This study aimed  to determine the psychological condition of students of the Al-Quran College of Science in learning Arabic, both students with  religious education background such as Aliyah/Islamic boarding schools and students with public schools background such as high schools, vocational schools. This study also  discussed the factors that  influenced  the psychological condition of students during learning  Arabic. This research is a qualitative descriptive study. The  data  were collected by  observation, interviews, and documentation. The process of data analysis is by examining all observed data from  related to Arabic learning, checking the validity of the findings by author participation. The conclusion from  this study can be argued that the psychological condition of STIQ Amuntai students in learning Arabic was  not good, they were less enthusiastic and confused when learning Arabic. It is due to several factors, namely:  diverse school backgrounds and lack  insights about Arabic such as a lack of management of Arabic learning materials. Beside that they were  faced with various other subject matter and the obligation to memorize al-Quran, thus the interest and enthusiasm gradually diminished. The  lecturer background  is in accordance with their education and the syllabus is in line  with  the campus syllabus.  The  teaching methods were not suitable for students abilities. Campus environment that did not  use Arabic both from superiors and students. There were inadequate facilities and infrastructure, such as language laboratories that were not used according to their function.